2016
DOI: 10.1021/acs.bioconjchem.6b00422
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation Tunable pH-Sensitive Phosphoramidate-Based Linkers for Controlled Release

Abstract: We developed a second generation of tunable pH-sensitive linkers based on our phosphoramidate scaffold to release amine-containing drugs under acidic conditions. The pH-triggered phosphoramidate-based linkers are responsive to pH and do not require intracellular enzymatic action to initiate drug release. On the basis of the model scaffolds examined, phosphoramidate-based linkers were selected for particular properties for controlled release applications such as amine type, stability under physiological conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…They also showed potential therapeutic activities and are known as potential alternative genetic systems (Gryaznov, 1999;Chen et al, 2009). Elaborate studies have been carried out in which phosphoramidate-based linkers, which are responsive to pH, do not require intracellular enzymatic action to initiate drug release (Choy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They also showed potential therapeutic activities and are known as potential alternative genetic systems (Gryaznov, 1999;Chen et al, 2009). Elaborate studies have been carried out in which phosphoramidate-based linkers, which are responsive to pH, do not require intracellular enzymatic action to initiate drug release (Choy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…14 Currently, several studies have demonstrated that the acidic condition in the tumor site is a promising means of eliciting drug release. [15][16][17][18] And, in our work, we found that drug molecules of Pt were preferentially released from the nanodrug in acidic conditions compared with the normal physical condition.…”
Section: Introductionmentioning
confidence: 55%
“…As anticipated, the rate of P−N bond hydrolysis of the payload-phosphoramidate system 1−3 followed pseudo-firstorder kinetics at all pH values (Figure 2B), consistent with our initial studies. 44,47,48 The rate constants (k 1 ) are summarized in Table 1. Importantly, there was no detectable hydrolysis observed for the modules at physiological pH (Figure 2C−E).…”
Section: Resultsmentioning
confidence: 99%